DEVELOPING EFL LEARNER'S SPEAKING ABILITY, ACCURACY AND FLUENCY THROUGH INTERACTIVE METHODS (Konferensiyalar | Conferences, 2024)
The article studies the implementation ways of Impromptu method into the classroom. It is fully proved the importance of Impromptu speech in teaching English language. The actuality of this article is the investigation of Impromptu method in the way of development of the speaking skills to provide communication in learning a foreign language and making EFL classroom more effective teaching environment as a facilitator.